The Family's Influences On Luke Chandler In John Grisham's A Painted House: A Behaviorist Approach - Hidayanto, Yusuf Arif (2004)
In this study, the researcher attempts to explore the influences of the family on the major character, Luke Chandler, in John Grisham's A Painted House. The objective of the study is to analyze John Grisham's A Painted House based on the structural elements and to analyze the major character's behavior based on the psychological approach, especially behaviorist perspective. In analyzing A Painted House, the writer uses the behaviorist approach and qualitative method. The object of the research is the behaviors of the major character derived from John Grisham's novel, published in 2001 by Dell Publishing Inc. The data are literary data that are divided into two categories: primary and secondary data. The primary data source is from the novel of A Painted House itself. While secondary data sources are from the books about behavioristic and theories of personality and the other materials, which related to the analysis. The method of data collection technique of this research is the library research. The data analyzing technique is using descriptive technique. The result of the study is that the family gives influences on Luke Chandler's behavior and personality. Each family member gives his or her own stimulus that makes Luke give responses toward the stimulus. The response is strengthened by the positive and negative reinforcement as well. The stimulus and reinforcement from the family affect the building of the major character's behavior and personality.